2016
DOI: 10.15847/obsobs1032016912
|View full text |Cite
|
Sign up to set email alerts
|

Establishing and Demonstrating US Hospital Brands Through Facebook

Abstract: Medical treatment, patient satisfaction, and hospital brand equity are positively related to three communication contexts: interpersonal, internal, and corporate. To integrate those contexts and expand that line of research, visceral analysis suggests that social media are transforming the impact of institutional communications conducted by hospitals. Specifically, questions continue to need answered to fill gaps in, clarify and reinforce previous research. To that end, this article analyzes the strategic impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
2
7
1
Order By: Relevance
“…Therefore, those with loyalty share good things about the hospital with others. This research supports the results which stated that hospital brand image has a positive influence on repeat visits and is a strong factor in combating negative news, which sometimes circulates in the community [Steele et al, 2000;Abubakar et al, 2017;Abubakar et al, 2016;Kaiser et al, 2020;Medina et al, 2016;Eiff and Wilfried, 2019;Sciulli, at al., 2015;Awua-Ikha and Kalu, 2018;Sharma, 2010].…”
Section: Positive Effect Of Hospital Brand Image On Patient Revisitsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, those with loyalty share good things about the hospital with others. This research supports the results which stated that hospital brand image has a positive influence on repeat visits and is a strong factor in combating negative news, which sometimes circulates in the community [Steele et al, 2000;Abubakar et al, 2017;Abubakar et al, 2016;Kaiser et al, 2020;Medina et al, 2016;Eiff and Wilfried, 2019;Sciulli, at al., 2015;Awua-Ikha and Kalu, 2018;Sharma, 2010].…”
Section: Positive Effect Of Hospital Brand Image On Patient Revisitsupporting
confidence: 86%
“…The results showed that the hospital's brand image positively affected patient repeat visits [Arici and Gucer, 2018; Kuipers et al, 2019;Awua-Ikhia and Kalu, 2018] and a substantial factor against negative news circulating in the community [Medina et al, 2016]. The establishment of brand image aims to increase public interest in visiting, influencing new consumers to select hospitals in seeking health services, and emotionally binding old patients, hence, they do not switch to competitors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For hospital organizations, social media is an excellent resource for spreading advertising on their products and services, as well as to communicate their mission and institutional vision (Huang & Dunbar, 2013). Facebook, in particular, due to its high number of followers, is a free tool that has commonly been used by hospitals to disseminate brand architecture (Medina et al, 2016) and increase its visibility (Coustasse & Slack, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the hospital Sant Joan de Dèu Hospital with the Clínica Universidad de Navarra (Spain), Costa-Sánchez and Míguez-González (2018) also confirmed that higher activity on social media does not imply higher levels of interaction with the public. In turn, Medina, Buil and Heath (2016) searched for the Facebook profiles of 300 hospitals in the United States (US) and observed that despite 282 of them maintaining an account, only 13 fulfilled at least 7 of the 10 indicators that were used to measure the quality of their activity on this platform. Huang and Dunbar (2013) detected that most of the profiles of US hospitals on Facebook and, above all, on Twitter instigated unidirectional communication.…”
Section: Introduction and State Of The Questionmentioning
confidence: 99%